An Interpersonal Metafunction Analysis of Some Political Advertisements - Lu’lu Atul Maknunah (Journal of English Education Program (JEEP), 2018)
This study presents the interpersonal metafunction analysis of some political advertisements. The advertisements consist of nine selected political advertisements and they contain of 31 clauses to analyze. This study is conducted to find out the result to the research question this study, which is saying “how is interpersonal metafunction represented in political advertisements”? In this study, the writer uses textual analysis with use the Systemic Functional Grammar (SFG) as the research instrument. The analysis of all political advertisements in this study consists of mood system, to which two kinds of mood system belong which consist of declarative, represented 22 times (70%) and Imperative used 9 times (30%). There is no interrogative mood system found.  Besides, there are three modalities found in the data analysis consisting of modal “will”, “may” and “should”. The first modal is “will” represented two times. The second modal is “may” which is used once and the last modal is “should” which is also presented once.